Basic french : total language study program - Kurbegov, Eliane (United States of America : McGraw-Hill Education, 2017)
Start learning French today with the digitally enhanced, premium edition of this bestselling workbook The bestselling-beginner level French workbook in the market-leading Practice Makes Perfect series is back and better than ever! Enhanced with comprehensive digital support, this new edition takes you to the next level with a unique set of tools and the time-tested Practice Makes Perfect approach. Broken into 50 short, manageable lessons with a focus on grammar and vocabulary, this workbook is your first step to learning the basics of the language. Engaging exercises across three-page units let you work at your own pace without becoming overwhelmed, as you learn the basics that first-year students are expected to know.
Chapter1. Definite articles- Family -- Chapter2. Clothing -Er verb endings -- Chapter3. Regular -re verbs - Common -re verbs -- Chapter4. BAGS adjectives - Locations -- Chapter5. Faire - Weather - Seasons -- Chapter6. Pouvoir - Adverbs -- Chapter7. Demonstrative adjectives - Common stem-changing -er verbs - Expressions of time -- Chapter8. Direct object pronouns - Gifts -- Chapter9. Irregular -ir verbs : sentir, sortir, partir, dormir - Adverbial phrases -- Chapter10. The family of prendre - Languages - Stress pronouns - Prepositional phrases .
Keywords: FOREIGN LANGUAGE STUDY -- FRENCH; FRENCH LANGUAGE VOCABULARY; TEXTBOOKS FOR ENGLISH SPEAKER